Using bacteria to make improved, nacre-inspired materials. Issue 8 (2016) - Schmieden, Dominik T.; Meyer, Anne S.; Aubin-Tam, Marie-Eve
ABSTRACT: Nacre (mother of pearl) is an attractive model for the development of new materials. Its sheet structure of alternating layers of calcium carbonate and an organic matrix confers it highly desirable properties such as high toughness and strength. In this study, we produce a nacre-inspired composite material using only bacterially-produced components. Calcium carbonate is crystallized via the action of ureolytic bacteria. After each crystallization event, we apply bacterially produced γ-polyglutamate (PGA) to the sample, which promotes layering compared to the PGA-free control. We show that the combination of these two compounds yields a layered material reminiscent of nacre, showing a way towards the biotechnological production of new, nacre-inspired materials.